Interactions of d10 metal ions with hippuric acid and cytosine. X-ray structure of the first cadmium (II)-amino acid derivative-nucleobase ternary compound - Capllonch, Maria Concepció (2001)
The interactions of Zn(II), Cd(II) and Hg(II) with hippuric acid (hipH) were studied and several novel compounds were synthesized and studied by NMR. Some new metal-hippuric-cytosine ternary compounds were formed and the structure of the [Cd(hip)2(cyt)(H2O)]2 ternary complex resolved. Each cadmium (II) atom has a distorted trigonal bipyramid coordination which is linked to a water molecule, a cytosine via N(3), a carboxylic oxygen atom of a hippurate moiety and two bridging dicoordinated hippurates bound through the carboxylic oxygen atoms. To these five main bonds, two longer ancillary interactions can be observed: the second oxygen of the monocoordinated hippurate group and the carboxylic oxygen of the cytosine ligand. The compound is stabilized by an intramolecular stacking between the benzene and cytosine rings and by the hydrogen bonds between the coordinated water molecules and the ligands. This is, to our knowledge, the first structure of a cadmium-amino acid derivative-natural nucleobase compound described so far.